Formation Of Aesthetic Consciousness Of 5-9 Class’ Schoolchildren - Serik Dayirbekov, Gulmira Dayirbekova, Gulnar Mussabekova,; Nurlan Babayev, Gulzhamal Jumadillayeva, (Opción, 2019)
The main objective of education is not only to achieve the formations of knowledge, skills and abilities, but also the formation of the pupil identity as the active citizen of the society. The leading method of the research is the modeling, allowing to consider this problem as the process of purposeful and conscious formation of aesthetic consciousness. As a result, after the forming experiment at schoolchildren: aesthetic consciousness was developed. In conclusion, schoolchildren have to be able to find necessary and suitable information for it, and for its independent development, they have to master various techniques and ways.